It is not possible to answer the question as it appears because it makes no sense whatsoever.
The sum of two positive integers is never zero. The sum of two numbers a and b can only be zero if a=-b, or a=0 and b=0. Since 0 is not a positive integer, and a and b cannot both be positive integers if a=-b, then it is impossible for the sum of two positive integers to be zero. _______________________________________________________________ The above answer is correct. Here is another way to say it: An integer is any whole number including negative numbers, positive numbers and zero. However, a "positive integer" is a whole number greater than zero. The "sum of two positive integers" means you are adding two numbers greater than zero together. Therefore, the sum of two positive integers can never be a negative integer, and can never be zero. Example: 1 + 1 = 2
int a = 1; int b = 2; int c = a + b; // Sum
addition a + b
The flowchart to read 10 positive integers K>10 Start A N K=1 Sum = 0 Sum = Sum + K2 B Is Y Print K > 100? sum K=k+1 End B A
Sine(A+ B) = Sine(A)*Cosine(B) + Cosine(A)*Sine(B).
a) BBr4 is incorrect b) CaCl2 is correct (Calcium chloride) c) SiF3 is incorrect d) KF2 is incorrect
641
On a multiple choice test with answers of A, B, C, and D, the answer of 'A' would only be the correct answer if all other choices are incorrect.
The associative property states that, for the sum of three or more integers the order in which the summation in carried out does not make a difference to the answer. Thus, for any three integers, A, B and C: (A + B) + C = A + (B + C) and so, without ambiguity, we can write either as A + B + C. Note that A + B need not be the same as B + A. The order of the integers DOES matter. It is the order of the summing that does not.
There are infinitely many answers: 1+a/b and 2-a/b for any pair of positive integers a and b, with a<b.
I assume you meant "sum". The answer is 60. 60=4 (integers) * 15 (average value of the integers). average of 4 integers = 15 --> (a + b + c + d)/4 = 15 --> (a + b + c + d) = 15 * 4 --> (a + b + c + d) = 60
Given:a + b = 2a - b = 8Then:a = b + 8∴ (b + 8) + b = 2∴ 2b = -6∴ b = -3∴ a = 5